PENGELOLAAN SISTEM DRAINASE OLEH DINAS PEKERJAAN UMUM DAN PENATAAN RUANG KOTA PEKANBARU TAHUN 2018 ( STUDI KASUS DRAINASE JL SALEH ABBAS PASAR BAWAH ) - Wulandari, Nova; M, Erman (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
The drainage system is a way of removing excess unwanted water in an area. With the drainage system, excess water can be channeled into the drainage channel. When the rainy season arrives, there will be puddles or flooding on the roads and also inundate the market area below. One of the factors in the occurrence of inundation is high rainfall, clogged drainage channels and cannot function properly. From this problem, it is necessary to manage damaged / problematic drainage channels so that the water flow can flow properly.This research was conducted with the aim of describing the management of the drainage system in Pasar Bawah Jl Saleh Abbas in 2018. This research is a case study research with a qualitative approach. The location of this research is the Public Works and Spatial Planning Office of Pekanbaru City. The data collection techniques used were interviews and documentation. The data analysis technique used is qualitative data analysis.The results of the study concluded that the Drainage System Management has not been running optimally, this is due to the unclear field responsible for handling this drainage problem and the absence of a special activity program so that the process in the activities carried out cannot be completed. Keywords: Management, drainage system